Inovasi Digital Model Rantai Pasok Pada Futuristik E-Commerce - Hutanti Setyodewi; Muhamad Albirra Arsyi Rizqi; Tegar Wahyudi Adha; Naufal Ibrahim; M Yoka Fathoni (Jurnal Informatika: Jurnal Pengembangan IT, 2021)
The increasing number of internet users in the world and especially in Indonesia has made traditional businesses start turning to technology such as e-Commerce. Where the increase in internet users by (±16%) and internet penetration by 75.47% between 2021 and 2022 are the main causes of a paradigm shift in society in Indonesia. Technology can play a role in helping management dynamics in a company's supply chain flow and entrepreneurial business activities in real-time. Human resources, cash flow, logistics, low-cost information flow, and efficiency play an important role in the continuity of technology-based business management. The application of Information Technology makes the supply chain process run according to consumer expectations to fulfill product distribution more efficiently and optimally. The concept of Technology-Based Supply Chain Management that has existed in recent years has become a priority for analysis in this journal, so that the qualitative research methodology used is a conceptual review, where this method collects data using library research methods and examines various related matters. information. to supply chains, behavioral changes, consumers, changes in the use of technology in e-Commerce which are the basis for determining innovation solutions to optimize Supply Chain Management (SCM) strategies on the concept of digital e-Commerce technology for future businesses.